Contribution to the eyed Sinella from China: two new species and additional reports on nine known species (Collembola: Entomobryidae) - Ding, Yin-Huan; Zhang, Feng (Zootaxa, 2015)
Two new 1+1 eyed species of Sinella Brook, 1882, S. uniseta sp. nov. and S. abietis sp. nov., are described from China. New collection records are reported for nine known species: S. qufuensis Chen & Christiansen, 1993, S. quinocula Chen & Christiansen, 1993, S. affluens Chen & Christiansen, 1993, S. wui Wang & Christiansen, 2000, S. umesaoi Yosii, 1940, S. gei Pan, Zhang & Shi, 2012, S. sunae Pan, Zhang & Shi, 2012, S. gracilis Zhang, 2013 and S. transoculata Pan & Yuan, 2013. Additions to original description, such as clypeal chaetae, chaetae along cephalic groove, and S-chaetotaxy, are provided for above known species. A key to the eyed species of Sinella from China is given.